Hubungan Pengetahuan Dan Sikap Remaja Tentang HIV/AIDS di Panti Asuhan Kota Padangsidimpuan Tahun 2018 - Siregar, Nurelilasari .; Pebrianthy, Lola .; Rangkuti, Nur Aliyah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
HIV / AIDS is still a very worrying thing, especially among adolescents who are at high risk of getting HIV / AIDS, one of the reasons is because of teenagers' ignorance about HIV / AIDS. Adolescent orphanages are among those who are vulnerable to risk because some orphanages experience economic hardship and rarely obtain health service information. This disease is caused by the Human Immunodeficiency Virus (HIV) which is transmitted through heterosexual contact, shared needles, mother to baby transmission, birth and breastfeeding, unsafe blood transfusion. To identify the relationship of knowledge and attitudes of adolescents about HIV / AIDS in the orphanage of Padangsidimpuan. This study uses a correlative descriptive design with a cross-sectional approach. Sampling was done with a total sampling technique of 96 people. Data analysis using chi square test. The results obtained by the majority of respondents with good knowledge as many as 80 people (83.3%), and positive attitudes as many as 82 people (85.4%) and minority of knowledge less as many as 16 people (16.7%), as much as negative attitudes 14 people (14.6%). And through the chi-square test results obtained with a value of p = 0.00, meaning that there is a significant relationship between knowledge and attitudes of adolescents about HIV / AIDS. This study proves that there is a meaningful relationship between adolescent knowledge and attitudes about HIV / AIDS